2011
DOI: 10.1007/s00271-011-0278-0
|View full text |Cite
|
Sign up to set email alerts
|

Bell pepper response to surface and subsurface drip irrigation under different fertigation levels

Abstract: A two-year field experiment was conducted in 2007 and 2008 to investigate different bell pepper responses to subsurface drip irrigation (SDI) and surface drip irrigation (DI) under four nitrogen levels: 0, 75, 150, and 300 kg/ha N (N 0 , N 75 , N 150 , and N 300 , respectively). Irrigation interval was set at 4 days. Bell pepper yield under SDI was significantly higher than that under DI by 4% in 2007 (13% in 2008). Water consumption under SDI was lower than that under DI by 6.7% in 2007 (7.3% in 2008). Mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 28 publications
3
27
0
Order By: Relevance
“…In our study, the rate of N application did not significantly affect the variation in soil moisture (Figures 2 and 3), which was consistent with the results of Kong et al [41]. On the other hand, the water movement was mainly influenced by the irrigation schedule under drip irrigation, which was similar to results of a previous study under flood irrigation [42].…”
Section: Movement Of Water For a Wheat Crop Under Drip Irrigationsupporting
confidence: 82%
“…In our study, the rate of N application did not significantly affect the variation in soil moisture (Figures 2 and 3), which was consistent with the results of Kong et al [41]. On the other hand, the water movement was mainly influenced by the irrigation schedule under drip irrigation, which was similar to results of a previous study under flood irrigation [42].…”
Section: Movement Of Water For a Wheat Crop Under Drip Irrigationsupporting
confidence: 82%
“…Patel and Rajput () also found that a better soil water regime in the root zone resulted in higher potato yields under the SDI system. Kong et al () found that NO3 − ‐N distribution in the root zone under SDI followed a parabolic curve and maintained higher NO 3 − ‐N concentrations at 20–40 cm soil depth. Increased availability of N at this depth, which is the active root zone of the crop, might be reponsible for higher crop yields under the SDI system.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to F1 fertigation level, the yields under F4 fertigation level increased from 8.0 to 27.0, 9.6 to 29.5, 11.5 to 33.7 and 10.8 to 30.1 t ha −1 under 0, 5, 10 and 15 cm depths of lateral placement, respectively. Increase in yield with increased levels of fertigation to a threshold level under DI and SDI has been demonstrated for vegetable crops such as bell pepper (Kong et al ., ), tomato (Sharda et al ., ; Silva et al ., ), cucumber (Zhang et al ., ) and broccoli (Thompson et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations